LncRNA SOX2OT rs9839776 Polymorphism Reduces Sepsis Susceptibility in Southern Chinese Children - Wu Z; Yu Y; Fu L; Mai H; Huang L; Che D; Tao J; Gu X (Dove Medical Press, 2020)
Zhiyuan Wu,1,* Yongqin Yu,1,* Lanyan Fu,2 Hanran Mai,2 Li Huang,1 Di Che,2 Jianping Tao,1 Xiaoqiong Gu2– 4 1Department of Pediatric Intensive Care Unit, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou 510623, People’s Republic of China; 2Department of Clinical Biological Resource Bank, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou 510623, People’s Republic of China; 3Department of Blood Transfusion, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou 510623, People’s Republic of China; 4Department of Clinical Laboratory, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou 510623, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoqiong Gu; Jianping Tao Email guxiaoqiong@gwcmc.org; golou6354@163.comBackground: Sepsis in children is one of the main causes of death in pediatric intensive care units (PICUs); however, the pathogenesis of sepsis is not fully clear. Previous studies revealed that many genetic variations were related to sepsis susceptibility. A long non-coding RNA SOX2 overlapping transcript (SOX2OT) may play a role in mitochondrial homeostasis and antioxidative activity, but the relationship between the lncRNA SOX2OT polymorphism and sepsis susceptibility has not been reported.Methods: In this study, 474 pediatric sepsis patients and 678 healthy controls were recruited from southern China. After genotyping, the strength of the associations was evaluated through odds ratios (ORs) and 95% confidence intervals (CIs).Results: The SOX2OT rs9839776 T allele was associated with decreased susceptibility to sepsis in southern Chinese children (TT/CT vs CC adjusted OR = 0.778, 95% CI = 0.610– 0.992; P = 0.0431). Moreover, the difference in susceptibility was greater in children of age > 60 months (adjusted OR = 0.458, 95% CI = 0.234– 0.896; P = 0.0225), survivors (adjusted OR = 0.758, 95% CI = 0.585– 0.972; P = 0.0358), males (adjusted OR = 0.655, 95% CI = 0.479– 0.894; P = 0.0077) and the sepsis subgroup (adjusted OR = 0.548, 95% CI = 0.343– 0.876; P = 0.0120).Conclusion: The rs9839776 T allele may contribute to decreased sepsis risk in Chinese children. Future studies with a larger sample size are needed to verify these results.Keywords: sepsis, SOX2OT, rs9839776, susceptibility, polymorphism